2013
DOI: 10.1063/1.4858736
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ripening stages on antioxidant properties of papaya fruit (Carica papaya L.)

Abstract: Abstract. Papaya (Carica papaya L. cv Eksotika) is one of the most commonly consumed tropical fruits by humans, especially Malaysians. The objective of this study was to determine the phenolic compounds and antioxidants activity in different ripening stages of papaya fruit. The fruits were harvested at five different, stages RS1, RS2, RS3, RS4, and RS5 corresponding to 12, 14, 16, 18, and 20 weeks after anthesis, respectively. Papayas fruit at five different stage of ripening were obtained from farms at Pusat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 16 publications
5
10
0
1
Order By: Relevance
“…AV gel facilitates the induction of phenylalanine ammonia lyase biosynthesis by flavonoids in fruit, which might be responsible for maintaining a high flavonoid content for a longer period of time [ 55 ]. These outcomes are in close agreement with those of other authors who applied different coatings on fruits and found them effective for preserving flavonoids content in tomato [ 56 ] and papaya [ 57 ]. Our results indicate that AV gels maintained quercetin and rutin contents during the storage period.…”
Section: Resultssupporting
confidence: 92%
“…AV gel facilitates the induction of phenylalanine ammonia lyase biosynthesis by flavonoids in fruit, which might be responsible for maintaining a high flavonoid content for a longer period of time [ 55 ]. These outcomes are in close agreement with those of other authors who applied different coatings on fruits and found them effective for preserving flavonoids content in tomato [ 56 ] and papaya [ 57 ]. Our results indicate that AV gels maintained quercetin and rutin contents during the storage period.…”
Section: Resultssupporting
confidence: 92%
“…The present investigation conforms with Ranjbar et al [41] reports that the nano-calcium treatment with the doses of 2.5% showed the maximum TPC compared to the control in apple and persimmon fruit [53]. Our findings are in line with those of Addai et al [24], who found that the amount of TPC had a significant effect on different harvesting stages of papaya fruits, and that the amount of TPC increased as maturity stages progressed. However, CaCl 2 increased the polysaccharide content in the fruit cell wall and maintained the strength of the cell membrane, which ultimately prevents the senescence-induced stress and delays the release or oxidize the phenolic compound from the fruit matrix [9].…”
Section: Total Phenolic Content (Tpc) and 22-diphenyl-1-picrylhydrazyl (Dpph)supporting
confidence: 93%
“…1 Whatman filter paper, and the supernatant was ready for DPPH (2,2-diphenyl-1picrylhydrazyl) and TPC (total phenolic content) determination. The supernatant was stored in the chiller pending the time the experiment would be carried out, and it is a slight modification of the methods reported by [24].…”
Section: Sample Extraction For Antioxidant Determinationmentioning
confidence: 99%
“…Chitosan coating on guava fruits facilitates the induction of phenylalanine ammonia-lyase pathway in fruit, which might be responsible for maintaining a high level of flavonoid content for a more extended period [41]. These findings are in close agreement with the results from other studies, which applied different coatings on fruits and found them adequate for maintaining or preserving the levels of flavonoids in papaya [42], and in tomato [43]. The findings of current research demonstrated that the doses of 1.5 and 2.0% chitosan treatments effectively maintain the levels of flavonoids and rutin.…”
supporting
confidence: 90%